Incidence and Antibiotics Resistance of Staphylococcus aureus isolated from Skin Lesion of Psoriasis Patients - Abbas, et.al, Ebtihal Chiad (Al-Qadisiyah Journal of Pure Science, 2017)
Isolation of Staphylococcus aureus was ought to be the reduced local defense factors in the lesion due to local and systemic immunosuppressant drugs like cytotoxic drugs and corticosteroid used for the treatment of psoriasis. The study aim to investigate the incidence and antibiotic resistance ability of these bacteria associated with psoriasis. Skin swab was taken from lesional skin of psoriasis patients for isolating of S. aureus. Isolates identified by conventional tests and confirmed with 16SrRNA specific primers. Among all patients, 37(52.9%) isolates were identified as S. aureus. All isolates tested for methicillin susceptibility using an initial screening test. The results showed 34(91.9%) isolates that resisted to pencillin, 29(78.4%) isolates resisted to methicillin and 22(59.5%) isolates that resisted to oxacillin. All isolates showed sensetivity to vancomycin and linezolid and then confirmed by used genotypic detection for presence of mecA gene. From this isolates, mecA gene was detected in 14 isolates. There were differences in resistance to antibiotics observed between mecA-positive and mecA-negative isolates.